2013
DOI: 10.1111/jog.12015
|View full text |Cite
|
Sign up to set email alerts
|

Survey of second‐trimester maternal serum screening in Japan

Abstract: This study revealed that most obstetricians in Japan do not provide their patients with sufficient information about MSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This limited time may result in informing patients insufficiently (Okuyama et al . ). Therefore, research focusing on the reasons behind pregnant women's lack of knowledge is essential to adjust the health care provided accordingly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This limited time may result in informing patients insufficiently (Okuyama et al . ). Therefore, research focusing on the reasons behind pregnant women's lack of knowledge is essential to adjust the health care provided accordingly.…”
Section: Discussionmentioning
confidence: 97%
“…In the same study, it was also reported that the time spent with each patient explaining the screening process in more than half medical facilities was less than five minutes. This limited time may result in informing patients insufficiently (Okuyama et al 2013). Therefore, research focusing on the reasons behind pregnant women's lack of knowledge is essential to adjust the health care provided accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The Committee stated that physicians should not give information about or recommend MSM to pregnant women because the capacity for genetic counseling (GC) was insufficient 12 . Nevertheless, there were a few centers with GC facilities that provided MSM in Japan 13,14 . There is still no consensus on prenatal testing for twin pregnancies in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…12 Nevertheless, there were a few centers with GC facilities that provided MSM in Japan. 13 , 14 There is still no consensus on prenatal testing for twin pregnancies in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many patients who underwent maternal blood screening for chromosomal abnormalities received inadequate genetic counseling. 4 The new technique of fetal cell-free DNA analysis may become the standard method in the near future. However, the procedure is currently in the developmental stage and requires careful evaluation in regard to ethics, the possibility of inadequate counseling, and the present suboptimal system for prenatal testing for genetic disorders.…”
mentioning
confidence: 99%